PENGARUH PAD, DAU, DAK DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI - Qomariyahti, Nova Dwi; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of Local Own Source Revenue, General Allocation Fund, Special Allocation Fund and Capital Expenditure toward the economy growth. This research applies secondary data in the form of budget realization report from each Local Government which has been collected from the Audit Board of Indonesia East Java Province and the economic growth data which has been collected from the Statistics Indonesia of East Java Province. The samples are 132 Districts / Cities in East Java and the data analysis has been carried out by using multiple linear regressions analysis. The result of the regressions analysis shows that Local Own Source Revenue, General Allocation Fund, and Special Allocation Fund give positive influence to the economic growth. Meanwhile the capital expenditure does not give any influence to the economy growth. The amount of R2 is 36.4% which can be explained by independent variables i.e. Local Own Source Revenue, General Allocation Fund, Special Allocation Fund and Capital Expenditure whereas the remaining is 63.6% which can be explained by other variables which are not included in the research models.Keywords: Local Own Source Revenue, Fiscal balance, capital expenditure, economy growth.